2014
DOI: 10.1063/1.4895913
|View full text |Cite
|
Sign up to set email alerts
|

Plannar light source using a phosphor screen with single-walled carbon nanotubes as field emitters

Abstract: We developed and successfully fabricated a plannar light source device using a phosphor screen with single-walled carbon nanotubes (SWCNTs) as field emitters in a simple diode structure composed of the cathode containing the highly purified and crystalline SWCNTs dispersed into an organic In2O3-SnO2 precursor solution and a non-ionic surfactant. The cathode was activated by scratching process with sandpaper to obtain a large field emission current with low power consumption. The nicks by scratching were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As an example, semiconducting SWNTs have been used to fabricate field-effect transistors (FET) [12][13][14]. As demonstrated by Misewich et al [12], optical emissions can be electrically induced from FETs (see Figure 2a,b).…”
Section: Single-walled Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, semiconducting SWNTs have been used to fabricate field-effect transistors (FET) [12][13][14]. As demonstrated by Misewich et al [12], optical emissions can be electrically induced from FETs (see Figure 2a,b).…”
Section: Single-walled Carbon Nanotubesmentioning
confidence: 99%
“…Therefore, through a convenient selection of CNTs according to their (n, m) indexes, these FET devices could be tailored according to the desired emission wavelength. Moreover, such devices could be also used as light absorbers, photovoltaic cells and photo-current generators (see Figure 2c,d), for example [15][16][17][18][19][20]; all of them with performances directly relying on the specific (n, m) choices [12][13][14][15][16][17][18][19][20]. The bridge between theory and commercial applications, which is the focus of the study of researchers working with the synthesis of carbon nanotubes, was a major problem in the advancement and consolidation of CNTs as a "next generation" material [2].…”
Section: Single-walled Carbon Nanotubesmentioning
confidence: 99%
“…Moreover, in the external EM field, CNTs behave as almost ideal one-dimensional nanorod antennas with a diameter of a few nanometers and length up to hundreds of micrometers, while single-walled CNTs (SWNTs) exhibit behavior similar to direct gap semiconductors with absorption spectra dominated by exciton lines [ 16 ]. The experimental observations of CNTs showed that the nonlinear behavior is related to a high third-order susceptibility with a picosecond recovery rate, which has been utilized in various promising applications, such as nanoscale light sources, photovoltaic devices, lasers, and recently also in various metamaterial designs [ 17 , 18 , 19 ]. Reports regarding the combination of metamaterial and photonic design with CNTs were presented by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…Light amplification in carbon nanotubes was experimentally demonstrated in the near-infrared wavelength range at cryo [3] and room temperatures [4], as a single photon emitter through dimensionality modification [5], by tuning the direct band-gap, controlling excitonic recombinations, and enabling exciton radiatively-decaying. Device examples of light emission from CNTs have previously demonstrated a p-n diode [6,7], tube to waveguidecoupling [8,9], flat plane-emission panels [10], and flexible light-emitting sources [11]. However, CNTs-based laser devices operating at a telecom wavelength, which are desired for on-chip optical interconnects, are not reported to date.…”
Section: Introductionmentioning
confidence: 99%